Antidiabetic and antihyperlipidemic activities of Cucumis melo var. momordica fruit extract on experimental animals - Arvind Kumar Srivastava; Alok Mukerjee; Abhishek Tripathi (SpringerOpen, 2020)
Abstract Background Diabetes mellitus is a major public health issue related to the irregular metabolism of carbohydrates, protein, and fat. It occurs due to insufficient insulin production and insulin action. Cucumis melo possesses several biological properties including antioxidant, anti-inflammatory, antibacterial, antihypothyroidism, and antiangiogenic activities. The objective of the present study was to determine the antidiabetic and antihyperlipidemic activities of Cucumis melo var. momordica fruit extract on experimental animals. Result Results show that treatment with C. melo fruit extract and fraction caused a reduction in blood glucose levels. Cucumis melo toluene fraction (CMTF) exhibited a significant (*P < 0.05) reduction of blood glucose level on the 28th day, i.e., 122 mg/dL, in comparison with the positive control group (streptozotocin (STZ)). However, the extract of C. melo showed less significant results in comparison with CMTF. Triglyceride, LDL, and VLDL levels were increased chronically due to STZ and were significantly (*P < 0.05) restored to 84.16, 86.97, and 19.73, respectively, by CMTF in comparison with the positive control group (STZ in the dose of 55 mg/kg). The extract-treated groups also showed similar results as CMTF, but their efficacy was lesser than CMTF. Conclusion It is can be concluded that C. melo fruits can be used as an effective antidiabetic and antihyperlipidemic drug. Graphical abstract